2004
DOI: 10.1074/jbc.m403206200
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Two Novel Radical S-Adenosylmethionine Proteins Required for the Assembly of an Active [Fe] Hydrogenase

Abstract: To identify genes necessary for the photoproduction of H 2 in Chlamydomonas reinhardtii, random insertional mutants were screened for clones unable to produce H 2 . One of the identified mutants, denoted hydEF-1, is incapable of assembling an active [Fe] hydrogenase. Although the hydEF-1 mutant transcribes both hydrogenase genes and accumulates full-length hydrogenase protein, H 2 production activity is not observed. The HydEF protein contains two unique domains that are homologous to two distinct prokaryoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
386
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(395 citation statements)
references
References 47 publications
5
386
0
4
Order By: Relevance
“…Gas exchange measurements showed that H 2 evolution occurs prior to CO 2 fixation upon illumination (Cournac et al, 2002). At light onset after a prolonged period in dark anoxic conditions, the photosynthetic electron flow is mainly a LEF toward hydrogenase , and lack of hydrogenase activity in hydrogenase maturation factor EF (hydEF) mutant strain deficient in hydrogenases maturation (Posewitz et al, 2004) induces a lag in induction of PSII activity . In cyanobacteria, the bidirectional Ni-Fe hydrogenase might also work as an electron valve for disposal of electrons generated at the onset of illumination of cells (Cournac et al, 2004) or when excess electrons are generated during photosynthesis, preventing the slowing of the electron transport chain under stress conditions (Appel et al, 2000;Carrieri et al, 2011).…”
mentioning
confidence: 99%
“…Gas exchange measurements showed that H 2 evolution occurs prior to CO 2 fixation upon illumination (Cournac et al, 2002). At light onset after a prolonged period in dark anoxic conditions, the photosynthetic electron flow is mainly a LEF toward hydrogenase , and lack of hydrogenase activity in hydrogenase maturation factor EF (hydEF) mutant strain deficient in hydrogenases maturation (Posewitz et al, 2004) induces a lag in induction of PSII activity . In cyanobacteria, the bidirectional Ni-Fe hydrogenase might also work as an electron valve for disposal of electrons generated at the onset of illumination of cells (Cournac et al, 2004) or when excess electrons are generated during photosynthesis, preventing the slowing of the electron transport chain under stress conditions (Appel et al, 2000;Carrieri et al, 2011).…”
mentioning
confidence: 99%
“…HydE is a member of the RS family and is essential for [FeFe]-hydrogenase maturation [6,29]. Several years ago, structures of TmHydE were reported from a crystal form that diffracted to high resolution (1.25 Å) [30].…”
Section: Hyde: 'A Riddle Wrapped In a Mystery Inside An Enigma'mentioning
confidence: 99%
“…In contrast, the [2Fe] H subcluster is held by a single protein ligand, a cysteine residue, but contains three carbon monoxides, two cyanides and an azadithiolate ligand [5]. The contrast between the sub-clusters extends to their assembly (Figure 1a), as the [4Fe-4S] H subcluster is synthesized and inserted by general Fe-S cluster biosynthetic machinery, however biosynthesis and insertion of the [2Fe] H subcluster requires the activity of highly specific maturase enzymes, HydE, HydG and HydF [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of [FeFe] hydrogenase (HydA), the reaction is catalyzed by the H‐cluster, which features a [4Fe4S] cluster coupled to an organometallic [2Fe] subsite (Figure 1 a) 2, 3, 4, 5. It is now well established that the biosynthesis of the H‐cluster is a two‐step process, in which the assembly of the [2Fe] subsite requires three HydA specific maturation proteins 6, 7, 8. The catalytic mechanism of this unique cofactor has been intensively studied and several catalytically active and non‐active states of the H‐cluster have been characterized 1, 4, 9, 10, 11, 12.…”
mentioning
confidence: 99%